HAZIR ELMA VE DOMATES SULARI İLE DOMATES SALÇALARINDAKİ ALTERNARİA TOKSİNLERİNİN BELİRLENMESİ - TOPDEMİR, AYKUT (Fırat Üniveristesi, 2010)
Bu çalışmada marketlerde satılan 10 farklı markaya ait domates salçası, domates suyu ve elma suyu olmak üzere toplam 30 gıda örneğinde Alternariol (AOH), Alternariol monometil eter (AME) ve Tenuazonik asit (TEA) miktarları HPLC'de (high pressure liquid chromatography) incelendi.

In this study, quantity of Alternariol (AOH), Alternariol monomethyl ether (AME) and Tenuazonic acid (TEA) in tomato paste, tomato juice and apple juice of 10 different brands were analyzed in HPLC (high pressure liquid chromatography).
The determination of alternaria toxins in apple and tomato juices and tomato paste
Keywords: Biyoloji